SETRATEGI KOMUNIKASI DALAM PROSES BHÂKALAN ETNIK MADURA DI DAERAH TAPAL KUDA - Akhmad Haryono (LITERA, 2018)
This article aims at describing the communication strategy used by Madurese ethnic members in Tapal Kuda regions in bhâkalan process.  For this aim, the linguistic approach was used in this research. The data were collected with participatory observation such as interview, recording, and documentary study. The collected data were then transcripted into the written data and analyzed using discourse analysis with pragmatic concept.  The research result indicated that Madurese  language (ML) used in bhâkalan  process constitutes ML variation of èngghi-enten (ML È-E) ,èngghi-bhunten (ML È-B), and ênja’-iya (ML Ê-I). The rhetorical style used in bhâkalan  process is indirect rhetorical style, that is figurative language. Pangadâ’ (delegation) is compared to vegetation, animal, and wind. Language variation (as politeness form) and rhetorical style are used as  communication strategy in  bhâkalan process.